Avoidable mortality among parents whose children were placed in care in Sweden: a population-based study. Issue 12 (4th August 2018) - Wall-Wieler, Elizabeth; Vinnerljung, Bo; Liu, Can; Roos, Leslie L; Hjern, Anders
Abstract : Background: Separation from one's child can have significant consequences for parental health and well-being. We aimed to investigate whether parents whose children were placed in care had higher rates of avoidable mortality. Methods: Data were obtained from the Swedish national registers. Mortality rates among parents whose children were placed in care between 1990 and 2012 (17 503 mothers, 18 298 fathers) were compared with a 1:5 matched cohort of parents whose children were not placed. We computed rate differences and HRs of all-cause and avoidable mortality. Results: Among mothers, deaths due to preventable causes were 3.09 times greater (95% CI 2.24 to 4.26) and deaths due to amenable causes were 3.04 times greater (95% CI 2.03 to 4.57) for those whose children were placed in care. Among fathers, death due to preventable causes were 1.64 times greater (95% CI 1.32 to 2.02) and deaths due to amenable causes were 1.84 times greater (95% CI 1.33 to 2.55) for those whose children were placed in care. Avoidable mortality rates were higher among mothers whose children were young when placed in care and among parents whose children were all placed in care. Conclusions: Parents who had a child placed in out-of-home care are at higher risk of avoidable mortality. Interventions targeting mothers who had a child aged less than 13 placed in care, and parents whose children were all placed in care could have the greatest impact in reducing avoidable mortality in this population.